1988
DOI: 10.1080/01904168809363856
|View full text |Cite
|
Sign up to set email alerts
|

Anescherichia colibioassay of individual siderophores in soil

Abstract: A bioassay system using mutant strains of Escherichia coli K12 was developed which can detect four different types of siderophores. These types are: ferrichrome and its analogs; enterochelin; coprogen, rhodotorulic acid, and ferrioxamines A, B, D 1 , and G; and a group of unidentified chelators which forms a part of E. coli's high affinity iron transport system. The amount of the four siderophore types in concentrated water extracts of bulk and rhizosphere soil from a field sample was estimated using this bioa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…The results demonstrate the role of the apoplasmic Fe pool in roots for Fe nutrition particularly of Strategy II plants. Higher concentrations of siderophores in the rhizosphere soil as compared with the bulk soil (Nelson et al, 1988) might provide a mean to increase apoplast loading and thereby indirectly Fe acquisition of soil-grown plants.…”
Section: ) Iron Uptake From Microbial Siderophoresmentioning
confidence: 99%
“…The results demonstrate the role of the apoplasmic Fe pool in roots for Fe nutrition particularly of Strategy II plants. Higher concentrations of siderophores in the rhizosphere soil as compared with the bulk soil (Nelson et al, 1988) might provide a mean to increase apoplast loading and thereby indirectly Fe acquisition of soil-grown plants.…”
Section: ) Iron Uptake From Microbial Siderophoresmentioning
confidence: 99%
“…These include, FepA for ferrienterobactin, Iut for ferric-aerobactin, FhuA, FhuE, and FhuF for the ferric-hydroxamate siderophores, ferrichrome, coprogen, and ferrioxamine, respectively, and FecA for ferricdicitrate (Braun et al, 1987;Nelson et al, 1988). After transport into the periplasm, subsequent transport of ferric-siderophores or ferric-dicitrate into the cytoplasm involves corresponding sets of cytoplasmic membrane proteins, including FepB, FepC, FepD, and FepG for ferrienterobactin, FecB, FecC, FecD, and FecE for ferric-dicitrate and three proteins designated FhuB, FhuC, and FhuD for ferric-hydroxamate siderophores.…”
Section: Generalized Mechanisms Of Fe Transport By Microorganismsmentioning
confidence: 99%
“…To determine which siderophores may be produced in the rhizosphere, we have developed bioassay procedures for quantification of different siderophore types (Nelson et al, 1988) and are now focusing on development of auxotrophic bacterial strains that can be used to detect various pyoverdin-type siderophores produced by Pseudomonas. Current procedures that involve water extraction of nonsterile soils are difficult to use quantitatively and have yielded very conservative data.…”
Section: Ecological and Soil Chemical Factors Affecting The Efficacy mentioning
confidence: 99%
“…Studies of marine systems have reported concentrations of strong iron complexing ligands between 0.3 and 7 nM (Gledhill and van den Berg, 1994;Gledhill et al, 1998;Powell and Donat, 2001;Rue and Bruland, 1997;van den Berg, 1995;Witter and Luther 1998;Wu and Luther, 1995). In soil solutions siderophore concentrations depend strongly on the soil horizons and higher concentrations occur in the rhizosphere compared to bulk soil (Bossier et al,1988 and references;Nelson et al, 1988). Also, field experiments with Pseudomonas fluorescens containing an iron-regulated promoter fused to an ice nucleation reporter gene showed that the production of siderophores is a function of soil pH in the rhizosphere as predicted from laboratory experiments (Loper and Henkels, 1997).…”
Section: Siderophore Concentrations In Natural Systemsmentioning
confidence: 99%